EL MITO DE LA DESCENTRALIZACIÓN TERRITORIAL (2019)
The present article aims to address the myth of territorial decentralization from a detailed analysis of the constitutional reformism; to this end, there will be a brief analysis of benefits and counterbalances of the flexible 1991 Constitution, constitutional reformism in terms of administrative decentralization, the high level of intergovernmental dependence, the phenomenon of tacit reform and their involvement in local and regional life and how the administrative autonomy of territorial entities, municipalities and departments has been diminished by the recentralizing phenomenon of the last governments. On the other hand, some brief recommendations will be determined, which, in any case, do not exhaust the institutional measures that must be addressed to save decentralization.